Motivasi dan Semangat Belajar Siswa Pada Pembelajaran PAI Studi Kasus di MTs Raudlatul Muta’allimin Babat Lamongan - Khoirul Umam; Imron Arifin (Peneliti.net, 2023)
This study will discuss the application of the Apperception Patron Client (APC) strategy in increasing student motivation and enthusiasm for learning